BIORREMEDIATION OF SOILS CONTAMINATED BY ORGANOCLORATED BY THE STIMULATION OF AUTOCONAL MICROORGANISMS, USING BIOSOLIDS - Durán Acosta, L.F.; Ladera Hernández, M.J. (Nexo Revista Científica, 2017)
The present investigation evaluated the process of bioremediation of organochlorine pesticides in a soil of the agricultural airport "The Picacho" of Chinandega's Department, Nicaragua, in that there are registered big concentrations of toxafeno. The biostimulation technique was used in the bioremediation process, using biosolids as source of essential nutrients for the microorganisms. The experimental design consisted of 2 completely randomized blocks, each one with 3 experimental units, contemplating 6 microcosms of soil. To every treatment one added different proportions of biosolids establishing relations soil:biosolid of 71:29 and 77:23. On having finished the treatments percentages of remediation were obtained between 84 % and 69 % respectively. This demonstrates the efficiency of the biosolids as source of nutrients for the metabolic stimulation of autochthonous microorganisms in the process of bioremediation of soils contaminated with toxafeno.